Draft Genome Sequences of Three Airborne Aspergilli Series Versicolores. Issue 1 (2nd January 2022) - Géry, Antoine; Séguin, Virginie; Bonhomme, Julie; Garon, David
Abstract: The Aspergilli of the section Nidulantes series Versicolores are among the most recurrent molds in indoor environments. These species cause damage to the quality of air. Indeed, they are responsible for allergies, aggravation of asthma and can even cause infections in immunocompromised patients. Molds belonging to the Versicolores series also produce sterigmatocystin, a mycotoxin classified as potential human carcinogen by the International Agency for Research on Cancer (group 2B). Here, we provide for the first time the genome of three species of the series Versicolores : Aspergillus creber, Aspergillus jensenii and Aspergillus protuberus which are the most abundant species of this series in bioaerosols. The genomes of these three species could be assembled with a percentage of completeness of 97.02%, 96.21% and 95.35% for Aspergillus creber, A. jensenii and A. protuberus respectively. These data will allow to study the genes and gene clusters responsible for the expression of virulence factors, the biosynthesis of mycotoxins and the proliferation of these ubiquitous and recurrent molds.